(untitled) (Sebha University Conference Proceedings, 2025)
This study aims to examine the flexural behavior of reinforced concrete (RC) beams containing waste strapping plastic belts as additional flexural reinforcement. Five beams specimens were prepared and tested until failure under the effect of flexural loading. First beam specimen is the control one without waste strapping plastic belts. The other four beams have the same reinforcement details as in reference one in addition to presence of waste strapping plastic belts as additional flexural reinforcement. The additional reinforcement are 2, 4, 8 and 12 strips . Load of first visible crack, ultimate load and midspan deflection were recorded for each tested beam. Percentage of ultimate load increasing for each beam was computed. Observations on general behavior, failure mechanisms and mode of failure were recorded. The experimental results refer to increase of flexural load carrying capacity in presence of plastic strips as additional flexural reinforcement. The maximum percentage was (34.7 %) for beam with (12) strips as compared with control beam .